IMPROVING THE QUALITY OF EDUCATION THROUGH MANAGEMENT REFORM DRIVERS IN HIGHER EDUCATION (Web of Teachers: Inderscience Research, 2024)
Quality management in higher education is driven by both the demands of public policy and the desire to enhance one’s market position, finds a new IIEP-UNESCO survey on quality management practices worldwide. Quality management is a long-standing and evolving practice in higher education worldwide. Yet, how its related processes and tools are designed and used has often been less clear, even to those within the university community. To help fill a major information gap on quality management, the UNESCO International Institute for Educational Planning (IIEP), with support from the International Association of Universities (IAU), conducted a trilingual survey. Garnering over 300 responses from universities worldwide, the resulting analysis features responses from a mixture of public and private and from all continents. One of the objectives was to better understand whether quality management is driven primarily by public policy or the desire of universities to enhance their market position. By understanding the catalyst, universities can be better supported in developing quality management that it is more aligned to their objectives.